2020
DOI: 10.1088/1361-651x/abb6de
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the naturally occurring forms of TiO2 on electronic and optical properties using OLCAO-MGGA-TBO9: a hybrid DFT study

Abstract: In this paper, a detailed study and analysis on the electronic and optical properties of anatase, rutile and brookite titanium dioxide (TiO2) which are the naturally occurring phases of TiO2 have been carried out. We have obtained these properties using the self-consistent orthogonalized linear combination of atomic orbitals with meta-generalized gradient approximation (MGGA) and Tran and Blaha (TBO9) as exchange–correlation under the framework of density functional theory. Obtained results on band gap value (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The integration over the entire Brillouin zone of momentum matrix elements between occupied and unoccupied wave functions gives the direct interband share in the dielectric functions imaginary part (ε 2 (ω)). ε 2 (ω) is evaluated using the equations given in [64].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The integration over the entire Brillouin zone of momentum matrix elements between occupied and unoccupied wave functions gives the direct interband share in the dielectric functions imaginary part (ε 2 (ω)). ε 2 (ω) is evaluated using the equations given in [64].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…From the obtained results, it implies that the dielectric function is square of the refractive index for both approaches. η(ω) and k(ω) both are related in terms of dielectric constant as represented by Kramers-Kronig [25].…”
Section: Statistical Investigation On Optical Properties Of Linbomentioning
confidence: 99%
“…Authors in [23] present DFT and DFT+U based calculations along with GGA and Heyd-Scuseria-Ernzerhof hybrid functional (HSE06) and found that stoichiometric LiNbO3 with HSE06 hybrid exchange-correlation functional widens the fundamental band gap concerning PBEsol at the cost of increased simulation time. Very recently, in our previous works [24][25][26][27][28], we have adopted OLCAO schemes in combination with PBES and TB09 to verify distinct phases of TiO 2 and recognized that outcomes are an approximation of experimental data. Evaluated data of Strontium Sulphide (SrS) by MGGA are the best match of experimental data while underestimation is induced by GGA and LDA [29].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the conduction band of TiO 2 is mainly composed of Ti 3d orbitals. [ 17,18 ] As for CN, N 2p orbitals play a decisive role in the formation of the valence band. The conduction band is principally composed of C 2p orbitals.…”
Section: Introductionmentioning
confidence: 99%